Task-Based Language Teaching: Perceptions and Implementation in Teaching Speaking - Tanty Prianty; Ngadiso Ngadiso; Agus Wijayanto (STAI Hubbulwathan Duri, 2022)
This study explores teachers' and students’ perceptions of task-based language teaching in teaching speaking and the teacher's techniques in implementing task-based language teaching in teaching speaking. This study employs an explanatory case study design with an English teacher and 35 students of vocational schools in Indonesia involved in this study. Semi-structured interviews and classroom observations were used to collect the data. The data were analyzed qualitatively using interactive models of Miles, Huberman, and Saldana (2014). The finding indicates that both teacher and students had a positive perception toward task-based language teaching, especially its implementation in speaking class. Implementing task-based language teaching in speaking classes makes the classroom environment more effective. The implication indicates that how the teacher sets the knowledge into classroom implementation is related to what the teacher has understood about task-based language teaching.